Influence of CoO Nanoparticles on Properties of Barium Zirconium Titanate Ceramics - Parkpoom Jarupoom (2018)
© 2017, The Minerals, Metals & Materials Society. Composites of Ba(Zr0.07Ti0.93)O3ceramic and CoO nanoparticles (at 1.0 vol.% to 3.0 vol.%) have been fabricated to investigate the effects of the CoO nanoparticles on the properties of the composites. X-ray diffraction data revealed that the modified samples contained Ba(Zr0.07Ti0.93)O3and CoO phases. Addition of CoO nanoparticles improved the magnetic behavior and resulted in slight changes in ferroelectric properties. The composites showed a magnetoelectric effect in which the negative value of the magnetocapacitance increased with increasing CoO concentration. Examination of the dielectric spectra showed that the two phase-transition temperatures as observed for unmodified Ba(Zr0.07Ti0.93)O3merged into a single phase-transition temperature for the composite samples. The composite samples also showed broad relative permittivity versus temperature (εr–T) curves with frequency dispersion. This dielectric behavior can be explained in terms of the Maxwell–Wagner mechanism. In addition, the Vickers hardness (Hv) value of the samples increased with increasing CoO content.